PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PENGOLAHAN PANGAN BERBAHAN LOKAL DI DESA JELANTIK KABUPATEN LOMBOK TENGAH - Humairo Saidah; Lilik Hanifah; Heri Sulistiyono; Shofia Rawiana; Agus Suroso (Jurnal Abdi Insani, 2023)
Jelantik Village has several community groups of tofu tempe producers, with each group's production capacity reaches 650 kg/day. As small-medium scale enterprises, the tofu tempe industry can employ the community, but the waste causes environmental problems. On the other hand, there are still many residents around the industry who are classified as economically weak. Along with the development of science and technology, pulp, a by-product of tofu and tempeh factories, has been extensively researched and modified for various nutritious processed foods. The training activity aims to empower the community around the factory, especially mothers, to use tofu waste in processed foods of high value, such as crackers, nuggets and sticks. Besides being abundantly available and cheap, tofu dregs still have good nutritional content. The training was carried out by transferring technical information on the manufacture of products to mothers in the environment around the tofu and tempeh factories. In addition to the manufacturing engineering process, the training also provides knowledge about packaging and marketing. The results obtained from this activity are that the community can use tofu dregs in crackers, nuggets and sticks. The community was enthusiastic about welcoming the team and eager to participate in the training process. The training can also answer some technical problems community in producing similar products. Currently, the assisted community groups have been able to produce crackers, nuggets and sticks made from tofu dregs and are preparing to form an entrepreneurial group together.